2016
DOI: 10.1111/dewb.12109
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Health Research Ethics in Nepal

Abstract: Unlike other countries in South Asia, in Nepal research in the health sector has a relatively recent history. Most health research activities in the country are sponsored by international collaborative assemblages of aid agencies and universities. Data from Nepal Health Research Council shows that, officially, 1,212 health research activities have been carried out between 1991 and 2014. These range from addressing immediate health problems at the country level through operational research, to evaluations and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 3 publications
(3 reference statements)
0
22
0
Order By: Relevance
“…Elsewhere we have charted the history of scientific research in the health sector in Nepal and its close ties to development aid (Sharma, Khatri and Harper 2016). Much of this research activity in the health sector is sponsored by bilateral aid agencies such as USAID and/or carried out by development institutions, often in collaboration with universities and research institutions.…”
Section: Evidence Generation In the Health Sector In Nepalmentioning
confidence: 99%
See 1 more Smart Citation
“…Elsewhere we have charted the history of scientific research in the health sector in Nepal and its close ties to development aid (Sharma, Khatri and Harper 2016). Much of this research activity in the health sector is sponsored by bilateral aid agencies such as USAID and/or carried out by development institutions, often in collaboration with universities and research institutions.…”
Section: Evidence Generation In the Health Sector In Nepalmentioning
confidence: 99%
“…These assemblages and institutional forms involving donors and their advisors (bilaterals; international non-governmental organisations (INGOs)), government policymakers, programme managers working for governments, INGOs, and NGOs, and researchers are not only critical in the generation of evidence but also provide much-needed networks of support for the successful up-scaling of pilot projects (Sharma et al 2016;Harper 2014). In Nepal, several NGOs and a few private research firms specialising in health systems research have emerged that mainly work on short-term sub-contractual agreements with the government, bilateral, multilateral, and private philanthropic organisations.…”
Section: Evidence Generation In the Health Sector In Nepalmentioning
confidence: 99%
“…A review of published studies from Sri Lanka revealed that only a third had documented ethics approval, 18 and a similar pattern is likely in other South Asian countries. Although ethics guidelines have been issued, [19][20][21][22][23] implementation and monitoring of compliance are inadequate and have led to instances of violation of rights of research participants, in particular disadvantaged groups of society. The context of disadvantaged groups must be considered when setting health research priorities to avoid harm, enable trust and participation, and maximise benefits for the entire society.…”
Section: Boosting Health Research In the Regionmentioning
confidence: 99%
“…Elsewhere we have charted the history of scientific research in the health sector in Nepal and its close ties to development aid (Sharma, Khatri and Harper 2016 This form of generation of evidence around programmatic interventions has been sustained by assemblages of local and international organisations and universities, and supported and funded by aid institutions. These assemblages and institutional forms involving donors and their advisors (bilaterals; international non-governmental organisations (INGOs)), government policymakers, programme managers working for governments, INGOs, and NGOs, and researchers are not only critical in the generation of evidence but also provide much-needed networks of support for the successful up-scaling of pilot projects (Sharma et al 2016;Harper 2014). In Nepal, several NGOs and a few private research firms specialising in health systems research have emerged that mainly work on short-term sub-contractual agreements with the government, bilateral, multilateral, and private philanthropic organisations.…”
Section: Introductionmentioning
confidence: 99%
“…). These evidence generation activities are dispersed and hidden under various programmatic interventions and it is almost impossible to map all the ongoing activities(Sharma et al 2016). There is no clear definition as to what is regarded as health research activity and thus what needs approval from the Nepal Health Research Council (NHRC) and what does not.…”
mentioning
confidence: 99%